Mere experience of low subjective socioeconomic status stimulates appetite and food intake - Cheon, Bobby Kyungbeom (2017)
Among social animals, subordinate status or low social rank is associated with increased caloric intake and weight gain. This may reflect an adaptive behavioral pattern that promotes acquisition of caloric resources to compensate for low social resources that may otherwise serve as a buffer against environmental demands. Similarly, diet-related health risks like obesity and diabetes are disproportionately more prevalent among people of low socioeconomic resources.